The Level of Servant Leadership by the Head of the Room and the Level of Burnout Syndrome Among Executive Nurses - Taofik, Rehieta Alifia; Sutresna, Iyos; Ridwan, Heri (Indonesian Journal of Global Health Research, 2024)
Hospitals are important health service facilities that pay special attention to their health workers, especially nurses because they have the largest segment in hospitals who are the spearhead of services with a greater amount of time and intensity than other health workers so that their performance will directly affect influences the roles and functions required to be able to provide maintained nursing services, efficiency and also have high service standards which refer to the occurrence of work stress and result in it burnout syndrome. Factors that cause it to occur burnout namely workload, feelings of self-control, rewards, alienation from the community, injustice, work stress, leadership style and desire to work. The appropriate leadership style to be able to deal with this is servant leadership. Objective: This research aims to determine the level of implementation of servant leadership by the head of the room and the level of burnout syndrome felt by the implementing nurses in the treatment room at Sumedang Regional Hospital. Method: The method used in this research is a correlational quantitative method. The research was conducted on implementing nurses using simple random sampling. This research instrument uses Barbuto and Wheeler's instrument to measure servant leadership and Maslach's instrument to assess burnout syndrome. This research has received ethical commission approval with No.11/EA/KEPK/2024. Results: This research obtained significance p 0.002 so that Hₒ is rejected, in other words there is a significant negative relationship between servant leadership of the head of the room and burnout syndrome in executive nurses. Conclusion: Servant leadership contributes to burnout syndrome because if the servant leadership of the head of the room is low then the burnout syndrome in executive nurses will be high, and vice versa.